KEBIJAKAN RESOLUSI KONFLIK TAMBANG BATU BARA DI KAWASAN HUTAN DI KALIMANTAN TIMUR - Rudi Subarudi; Hariadi Kartodihardjo; Sudarsono Soedomo; Hadiyanto Sapardi (Jurnal Analisis Kebijakan Kehutanan, 2016)
East Kalimantan has coal deposits of 37.5 billion tons and its coal business is very complex with numerous conflicts happened in the field. The objectives of the study were as follows: (i) to review the progress of coal mining business, (ii) to analyse the legal license of coal mining, (iii) to  identify overlapping policies on coal mining, and (iv) to  formulate policies on conflict resolution of coal mining in the forest areas. The results of study showed that annual coal production and export achieved 192.97 million tons and 145.82 million tons, respectively. At present, the number of coal mining business in the forest achieved 159 units which cover forest areas of 362,061 ha. However, the number of unprocedural coal companies reached 223 units with an area of 774,519 ha, or twice the legal business unit.  Conflict cases of coal mining in the forest areas are mainly due to poor  governance licensing, that trigger the conflict between mining companies and forest companies in the field due to overlapping operational area. Five recommended actions should be considered in order to resolve conflicts of coal mining in the forest areas, namely, implementation of monitoring, controlling and law enforcement, regulation harmonization, implementation of good mining governance, implementation of good communication and coordination, and implementation of one map policy.